2022
DOI: 10.1111/jhn.13021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D3 supplementation on cardiometabolic disease risk among overweight/obese adult males in the UK: A pilot randomised controlled trial

Abstract: Background: Observational studies suggest links between reduced serum 25(OH)D concentration and increased cardiometabolic disease risk. However, these studies provide limited evidence of causation, with few conclusive randomised controlled trials (RCT) having been carried out to date. This RCT investigated the effect of vitamin D 3 supplementation on vascular function and cardiometabolic disease risk markers, in 55 healthy males aged 18-65 years with plasma 25(OH)D concentration <75 mol L -1 and body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In our participants, the 12-week RT and supplementation period had no impact on fasting serum glucose or insulin levels or HOMA-IR. This finding is consistent with the data from other researchers [22,86] who evaluated the possible combined effect of Vit-D supplementation and RT on insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…In our participants, the 12-week RT and supplementation period had no impact on fasting serum glucose or insulin levels or HOMA-IR. This finding is consistent with the data from other researchers [22,86] who evaluated the possible combined effect of Vit-D supplementation and RT on insulin resistance.…”
Section: Discussionsupporting
confidence: 93%
“…37 In addition, trials are often powered on noncardiometabolic outcomes. 18,35 Even meta-analyses of randomised controlled trials within this scope have limitations due to bias in the selection of participants and comparability of study groups and a limited selection of CVD-related outcomes. 20,33,38,39 Only one study found a significant effect with a 16% (0.22 mmol/L) decrease in serum triglycerides in those given vitamin D compared to the placebo group but an 8% (0.28 mmol/L) increase in serum LDL.…”
Section: Discussionmentioning
confidence: 99%
“…These include significant heterogeneity of study design–related factors (such as vitamin D status at baseline, vitamin D doses and form of supplement given, therapy duration, skeletal outcomes), as well as individual differences in absorption and metabolism, genetic differences in the vitamin D receptor as well as biases due to different diseases and several potentially confounding factors including age, body fat, medications, diet and physical activity 37 . In addition, trials are often powered on non‐cardiometabolic outcomes 18,35 . Even meta‐analyses of randomised controlled trials within this scope have limitations due to bias in the selection of participants and comparability of study groups and a limited selection of CVD‐related outcomes 20,33,38,39 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations